Assessment of Occupation-Related Lower Limb Venous Disorders Using Doppler Ultrasonography: A Cross-Sectional Study: Occupation-Related Lower Limb Venous Disorders Using Doppler Ultrasonography - Kiran, Warda; Noreen, Kashmaila; Arshad, Nosheen; Mohsan, Maria (Pakistan BioMedical Journal, 2025)
The lower limb contains the hip, femur, knee joint, tibia, fibula, and foot. Some common abnormalities of lower limbs are varicose veins, followed by deep vein thrombosis, fractures, tumors, etc. Objectives: To evaluate lower limb venous abnormalities in patients related to their occupation using Doppler ultrasonography. Methods: This was a descriptive cross-sectional study conducted within the Radiology Department. A high-frequency linear probe, a TOSHIBA ultrasound machine, and the patient table were used in the equipment for this study. The patients were included after written consent. A sample size of 117 patients was considered using a convenience sampling technique. All patients with lower limb pain, swelling, tortuous veins, and tenderness were included in the study. The data were entered and analyzed using SPSS version 26.0. Results: Lower limb abnormalities are most common at the age of 41-50 years, 46 (39.3%). There were 75 (64.1%) male in the study and 42 (35.9%) female in the study. Most of the patients, 41 (35.0%), were housewives, followed by businessmen, 4 (20.5%). Superficial femoral vein 55 (47.0%) was involved in most patients. The most common diagnosis was varicose veins, 71 (60.7%), followed by deep vein thrombosis (DVT), 32 (27.4%). Lower limb venous abnormalities are seen to be more common in male than in female. These abnormalities are common at the age of 41-50 years. Conclusions: In conclusion, the most common occupation is seen to be housewives. The most common venous abnormality was left-sided varicose veins, followed by Deep Vein Thrombosis.